1994
DOI: 10.1089/hyb.1994.13.373
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibody Specifically Reacting against 73-Kilodalton Heat Shock Cognate Protein: Possible Expression on Mammalian Cell Surface

Abstract: The heat shock proteins (hsp) are regarded as being immunogenic to the animal hosts. Although certain hsp are suggested to be expressed on the cell surface, further evidence for the cell surface expression of these proteins has been required. In this article we report the development of a MAb NT22. This antibody reacted with ATP-binding proteins (which contain a large amount of 70-kDa hsp family) of HeLa cells, and with purified bovine 70-kDa hsp. It did not react with the E. coli lysate, but clearly reacted w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…MAb OC.10 reacted strongly with PepSPOTS 1-8 and 15-17 that correspond to amino acids 340-366 and 368-384, respectively hepatocytes. Although there have been previous reports describing cell surface expression (Tsuboi et al 1994;Hirai et al 1998;Fishelson et al 2001), little is known regarding the orientation of Hsc70 in the plasma membrane or how this well-described cytoplasmic protein localizes to the cell surface. Previously, Hirai et al (1998) identified a monoclonal antibody that recognized an epitope spanning amino acid residues 350-372 of the Hsc70 ATPase domain and confirmed by FACS analysis that this reactive epitope was expressed on the surface of Daudi cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MAb OC.10 reacted strongly with PepSPOTS 1-8 and 15-17 that correspond to amino acids 340-366 and 368-384, respectively hepatocytes. Although there have been previous reports describing cell surface expression (Tsuboi et al 1994;Hirai et al 1998;Fishelson et al 2001), little is known regarding the orientation of Hsc70 in the plasma membrane or how this well-described cytoplasmic protein localizes to the cell surface. Previously, Hirai et al (1998) identified a monoclonal antibody that recognized an epitope spanning amino acid residues 350-372 of the Hsc70 ATPase domain and confirmed by FACS analysis that this reactive epitope was expressed on the surface of Daudi cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although prior observations demonstrating cell surface localization of Hsc70 have been reported (Tsuboi et al 1994;Hirai et al 1998;Fishelson et al 2001), little is known regarding the orientation of the protein at the cell surface. Furthermore, the morphogenic changes induced in situ by MAb OC.10 ( Fig.…”
Section: Epitope Mapping Of Mab Oc10mentioning
confidence: 99%
“…Thus, hsp70 and hsp90 have been located on cell surfaces of tumour cells and tumour cell lines (Konno et al, 1989;Ferrarini et al, 1992;Tsuboi et al, 1994;Multhoff et al, 1995) as well as on the surface of peripheral blood cells in SLE patients (Erkeller-Yuksel et al, 1993). Similarly, Jameel et al (1992) originally identified the altered expression of hsp90 in breast cancer on the basis of its isolation with an antibody prepared to breast membrane preparations, again suggesting the appearance of this protein on the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…On day 8, the expanded V65(ϩ) lymphocytes were fused with mouse BW5147 TCRαβ(−) cell line and seeded in 96-microwell-plates with HAT (SIGMA, St. Louis, Mo., U.S.A.) medium. The protocol of hybridization between cells was described earlier (8,25). Briefly, approximately 2ϫ10 8 lymphocytes were fused with 4ϫ10 7 BW5147 cells by polyethyleneglycol 4000.…”
Section: Methodsmentioning
confidence: 99%